Methodology for the management of risk in the storage and transport of hazardous substances - Concepción Maure, Lissette; Goya Valdivia, Félix Abel; Coello Machado, Norge Isaías; Glistau, Elke (My University, 2019)
The decision making has great importance in the formulation of prevention and recovery policies against technological accidents in the chemical process industry and companies that handle hazardous substances. The main objective of management of technological risks in storage and transport activities along the supply chain, is the search of alternatives to reduce or mitigate the major hazards without eliminating the obtaining of benefits. The objective of this research is to develop a general procedure and its methodological instruments for the management of risks of major accidents in activities of storage and distribution of hazardous substances. It includes multicriteria analysis, risk measurement methods and control tools to identify, characterize and hierarchize the storage areas and distribution routes of greater danger. The application of the procedure enables the reorientation of organizational efforts supported by information technologies and ensures a continuous improvement approach. This research takes as case of practical study the logistics network of Fuel Trading Company of Villa Clara and uses the strategy of multiple explanatory cases in different companies that operate with hazardous substances in the province. As a result, a ranking was obtained of the activities where dangerous substances are manipulated, for the execution of evaluation and mitigation actions.
Keywords: Risk Management; Hazardous Substances; Multicriteria Analysis; Control Tools